1978
DOI: 10.1007/bf01350109
|View full text |Cite
|
Sign up to set email alerts
|

Longevity among blowfliesPhormia terraenovae R.D. kept in non-24-hour light-dark cycles

Abstract: From the day of hatching, groups of about 150 blowflies Phormia terraenovae R.D. were continuously subjected to light-dark cycles (LD) of constant duration, ranging from 20 to 28 h (zeitgeber period T), or to constant illumination (LL). Survival was determined by the number of days after which only 10% of the flies in each group were still alive, and expressed as percent of the survival of a control group kept in T=24 h. With T equal to 25, 26 or 27 h, survival was 100%; it was reduced to about 90% in T=23 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(33 citation statements)
references
References 16 publications
3
30
0
Order By: Relevance
“…Fruitflies [10] and blowflies [11] live longer under a 24 h light-dark cycle than under various other periods or under continuous light conditions. Tomatoes grow faster under a 24 h light -dark cycle than under shorter or longer cycles or even in continuous light [12 -14].…”
Section: Empirical Evidence For a Selective Advantage Of Circadian Rhmentioning
confidence: 95%
“…Fruitflies [10] and blowflies [11] live longer under a 24 h light-dark cycle than under various other periods or under continuous light conditions. Tomatoes grow faster under a 24 h light -dark cycle than under shorter or longer cycles or even in continuous light [12 -14].…”
Section: Empirical Evidence For a Selective Advantage Of Circadian Rhmentioning
confidence: 95%
“…In insects, adult lifespan is significantly reduced because of deleterious effects of light, including that of LL or non-24 h LD cycles (Pittendrigh and Minis, 1972;von Saint-Paul and Aschoff, 1978), while DD is known to stimulate the defense system and enhance adult lifespan (Shostal and Moskalev, 2013). Similarly, a few other studies have reported higher adult lifespan in flies maintained under DD compared with those kept in LD or LL (Allemand et al, 1973;Sheeba et al, 2000).…”
Section: Adult Lifespanmentioning
confidence: 99%
“…Disruption of circadian timing systems results in reduced reproductive output in the gypsy moth, Lymantria dispar (Giebultowicz et al, 1990), and D. melanogaster (Beaver et al, 2002;Beaver et al, 2003), shortening of adult lifespan in D. melanogaster (Hendricks et al, 2003;Kumar et al, 2005), reduction in vegetative growth and survivorship in Arabidopsis thaliana (Dodd et al, 2005), and increased predation in free-living ground squirrels Spermophilus lateralis (DeCoursey et al, 1997) and chipmunks Tamias striatus (DeCoursey et al, 2000). Furthermore, circadian clocks in resonance with environmental light/dark (LD) cycles have been shown to enhance adult lifespan of D. melanogaster (Pittendrigh and Minis, 1972;Klarsfeld and Rouyer, 1998) and blow flies Phormia terraenovae (von Saint Paul and Aschoff, 1978), and competitive ability in cyanobacteria Synechococcus sp. (Ouyang et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the blowflies held under a LD 12:12 photoperiod, shifting the light phase every week for 6 h, lowered their average life span from 125 (con trol) to 98 days. Furthermore, their survival rate declined from 75 to 52% when kept in LL [19]. Regarding mammals, Halberg [20] placed BALB/c mice under a LD 12:12 cycle and altered the LD phase for 180° (LD 12:12 to DL 12:12) every week for 2 years; the mouse life span was reduced to 88.6 ± 2 weeks compared to 94.5 ± 2 weeks of the con trol group.…”
Section: %mentioning
confidence: 99%